Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada PT. Mas Agung Sejehatera Unit Kedungdung Sampang - Moh. Herman Djaja; Runik Puji Rahayu (Assyarikah: Journal of Islamic Economic Business, 2022)
This research is a quantitative descriptive study using a sample of 93 customers, taken from the study population. The research location is at PT. Mas Agung Sejehatera Kedungdung Sampang Unit. Sampling using random sampling technique. the test equipment used to test the research instrument is in the form of a validity test and a reliability test. The analysis technique uses multiple regression techniques. The results show that the coefficient of determination R Square is 0.870 or 87.0% which indicates that the increase in customer satisfaction is influenced by Responsiveness (X1), Assurance (X2) and Physical Evidence (X3), while the remainder is (100% - 87.0%) = 13.0%) influenced by other factors not examined in this study. The results of calculations using the F test obtained F count of 17.431 and when consulted with F tables of 2.47 showed F count > F table. So the author's hypothesis is that responsiveness (X1), assurance (X2) and physical evidence (X3) are suspected simultaneously to the dependent variable, namely customer satisfaction (Y) at PT. Mas Agung Sejahtera Kedungdung Unit. The calculation results obtained t count for the Responsiveness variable (X1) of 1.048 and if consulted with t table of 1.661 obtained t count <t table. Guarantee variable (X2) of 0.273 and if consulted with t table of 1.661 obtained t count <t table. Whereas for the Physical Evidence variable (X3) the t value is 7.775 and if consulted with a t table of 1.661 it is obtained t count > t table, it can be concluded that the Physical Evidence variable (X3) has a partial effect on Customer Satisfaction (Y) at PT. Mas Agung Sejahtera Kedungdung Unit can be proven. From the results of calculations using the t test, it turns out that of the three variables, the Physical Evidence variable (X3) has the greatest t value, which is equal to 7.775.